Severe equestrian injuries: A seven-year review of admissions to a UK major trauma centre. (January 2023) - Gharooni, Aref-Ali; Anwar, Fahim; Ramdeep, Romann; Mee, Harry
Background: Equestrian sports are regaining popularity in the United Kingdom. Due to horses' considerable weight and speed, serious injuries can occur. Riding style and equipment differ between North America and the United Kingdom with previous studies focusing on the former. Objective: This study aims to assess the pattern of horse-related injury admissions to a major trauma centre in the United Kingdom. Methods: A retrospective study of our hospital's trauma registry between years 2012 and 2020 was performed. Cases included those admitted for severe horse-related injuries (irrespective of age/sex) with Injury Severity Score (ISS) of ≥ 4. Demographics, injury characteristics (ISS, Glasgow Coma Scale (GCS), injury region and operations), hospital stay and Glasgow Outcome Scale (GOS) on discharge were extracted. Four groups were formed based on mechanism of injury: fall from horse, fall and horse landing on top (FL group), kicked, and fall and kicked (FK group). Comparisons in injury and outcomes were analysed between these groups. Results: 301 (2.8%) eligible cases were identified from 10, 911 cases. 70.8% were female with mean (± SD) age of 42.7 (± 16.5) years. Most common mechanism of injury was fall (72.8%) then kicked (14.6%) with groups FL and FK forming < 10% each. No significant difference was found between the groups initial GCS, ISS, total or ICU length of stay and GOS ( p > 0.05). Most common regions of injury were orthopaedic (41.9%), spinal (26.2%), thoracic (20.1%) and head injuries (19.3%). 75% had good recovery on GOS though there were 3 fatalities relating to severe traumatic brain injury. Conclusion: Orthopaedic limb injuries form the majority of horse-related injuries which contrasts the 1970s where head injury prevailed which is likely due to the widespread use of better head protection. Consideration should be given to enhanced limb safety equipment to prevent injury.